Need for Cognition as an Antecedent of Individual Innovation Behavior - Wu, C.; Parker, Sharon; de Jong, J. (Sage Publications, Inc., 2014)
© The Author(s) 2011. The authors propose that need for cognition, an individual’s tendency to engage in and enjoy thinking, is associated with individual innovation behavior. Moreover, drawing on an interactionist perspective, the authors suggest that need for cognition becomes more important when individuals face lower job autonomy and time pressure in their work. This is because, when these job characteristics are low, there is no contextual driving force for individual innovation, so personality has a stronger influence. In a multisource study of 179 employees working in a Dutch research and consultancy organization, the authors’ expectations were largely supported. They found that need for cognition was positively associated with peer-rated innovation behavior, as were job autonomy and time pressure, even when controlling for openness to experience and proactive personality. Furthermore, the relationship between need for cognition and innovation behavior was strongest for individuals with low job autonomy and low time pressure and indeed was nonexistent at high levels of these contextual variables. This study, therefore, suggests that context can substitute for an individual’s need for cognition when it comes to individual innovation.